Inclusiveness through art films in Telugu: A modern to postmodern analysis of K. Viswanath's films. Issue 3 (1st December 2014) - Murthy, C. S. H. N.
This present study attempts to situate the themes of Kasinadhuni Viswanath's (popularly known as K.Viswanath in Telugu film industry) musicals in modernist and postmodernist cultural perspectives in an effort to show that art forms such as music, song and dance are of immense help for a silent and non-violent social revolution that subsumes the 'inclusiveness' besides ushering in harmony in society. Viswanath's films are synonymous with the repertory of music and dance forms in India. Known for his artistry in combining music, song and dance together, Viswanath's reputed and award winning film – Sankarabharanam (1979) – has not only won national recognition as the best entertaining wholesome popular film, but also offered explorable alternatives to eliminate social evils such as economic and caste disparities, and the misconceptions such as, western music is superior over eastern music, western life is greater than traditional Indian life, etc. Viswanath is perhaps one of the rarest directors of the Indian film industry who dared to produce a different genre of films, both in Telugu and Hindi, combining music and dance forms against the background of social or traditional issues for national integration (e.g. Saptapadi 1981). Using the moving image and analysis of Kracauer, this study heuristically offers evidence to show how his musicals have effectively used a 'social model' akin to a 'Gandhian model' through a unique combination of signs, symbols and philosophical ideas of traditional Indian culture with the art forms – music, song and dance styles. Further the study endeavours to show how Viswanath develops conflicts first at the modernist level between the Proppian elements in his plots in the narratives, and how through a deft manoevouring of the narratives these conflicts culminate into solutions suggestive of 'inclusiveness'.